The Effect of Corporate Social Responsibility on Investment Decisions: The Mediating Role of ESG Score on Banking Companies in Indonesia - Fadhia, Husnuzzahra; Rahma Elika, Dirda; Dian Pratiwi, Permata (Dinasti Publisher, 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) on investment decisions in Indonesia's banking sector, considering the role of the ESG (Environmental, Social, Governance) Score as a mediating variable. A quantitative approach is used, involving eight banking companies listed on the Indonesia Stock Exchange (IDX) and included in the IDX ESG Leaders index from 2019 to 2023, with a total sample of 40 research samples. The research findings indicate that CSR disclosure does not have a direct effect on investment decisions. However, ESG mediation significantly impacts CSR and investment decisions, and ESG is associated with EPS. These results suggest that ESG can act as a bridge for CSR in investment decision-making.